2019
DOI: 10.1108/ijbm-11-2017-0245
|View full text |Cite
|
Sign up to set email alerts
|

Customer centricity in mobile banking: a customer experience perspective

Abstract: Purpose-The purpose of this paper is to increase understanding about how to improve customer value and to make mobile banking services a profitable business for banks and other financial actors. The study explores the user experiences and related value of a new mobile banking service. Design/methodology/approach-The study is implemented as a case study that is phenomenological in nature and linked to an interpretive consumer study. Empirical data were collected through 14 semi-structured theme interviews and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 53 publications
2
69
0
9
Order By: Relevance
“…Komulainen and Saraniemi (2018) concluded that the experience obtained from the use of mobile banking in banking have a relationship to each other in creating satisfaction to banking customers. It is also in line with research conducted by Komulainen and Saraniemi (2018) which shows that the interaction between services and users, namely the process of customer experience as experienced by users, creates value for users.…”
Section: E-service Quality Has a Positive And Significant Influence On E-satisfaction In Using Mobile Banking Through The User Experiencesupporting
confidence: 84%
See 1 more Smart Citation
“…Komulainen and Saraniemi (2018) concluded that the experience obtained from the use of mobile banking in banking have a relationship to each other in creating satisfaction to banking customers. It is also in line with research conducted by Komulainen and Saraniemi (2018) which shows that the interaction between services and users, namely the process of customer experience as experienced by users, creates value for users.…”
Section: E-service Quality Has a Positive And Significant Influence On E-satisfaction In Using Mobile Banking Through The User Experiencesupporting
confidence: 84%
“…One of the services provided banking in the era of the time mobile banking. The emergence of mobile banking as one of the innovations that further simplify the banking activity because it eliminates the boundaries of space and time (Komulainen and Saraniemi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Digitalization involves more than just the mere conversion of documents from paper to an electronic formatdigitization (Gobble, 2018). Broadly, digitalization means adopting a broader change mindset or perspective that encompasses data, digital technology and human-centered design to transform the business model (Følstad and Kvale, 2018;Ghobakhloo, 2018;Komulainen and Saraniemi, 2019;Lin et al, 2018). It includes embracing new ways of doing business, using new capabilities to serve customers and designing organizational processes to become more agile (Dörner and Edelman, 2015).…”
Section: Digitalization Megatrend and Digital Competenciesmentioning
confidence: 99%
“…Customer experience is a topic that demands to be studied using the correct information to satisfy the customer's requirements (Vinayak & Kodali, 2013;Maklan, Antonetti & Whitty, 2017). This phenomenon is a wide construct that embraces correlations between customer satisfaction and service quality, to create value to firms; value determined by users that are comparing an experience received as a result of the interaction with the key performance indicators assigned by one enterprise (Nobar & Rostamzadeh, 2018;Komulainen & Saraniemi, 2019). "The challenge of implementing experience successfully is that it is defined so broadly-so "holistically"-as to exclude almost nothing [and turn it into] the theory of everything" (Maklan, Antonetti & Whitty, 2017, p. 93).…”
Section: Introductionmentioning
confidence: 99%